Permeability evaluation of Industry 4.0 technologies in cloud-based energy management systems environments - Energy Cloud - Jones Luís Schaefer; Patrícia Stefan de Carvalho; Augusto Ruhoff; Johanna Dreher Thomas; Julio Cezar Mairesse Siluk (Production)
Abstract: Paper aims This article aims to diagnose the penetration level of Industry 4.0 technologies in cloud-based energy management systems, the Energy Cloud. Originality The energy sector is undergoing a technological evolution driven by the integration of Industry 4.0 technologies with energy management systems, making relevant the study of the permeability of these technologies with energy companies. Research method The research used two articles on Energy Cloud as a theoretical basis and a data collection carried out with managers of renewable energy companies, with the data being analyzed using the MONNA software. Main findings The results show that there is a greater understanding and use of the Internet of Things and Sensors technologies to the detriment of Cloud Computing and Big Data. Implications for theory and practice The article shows that there is a need for managers to seek greater familiarization, especially with Cloud Computing and Big Data.